Smart card research and advanced applications : 15th International Conference, CARDIS 2016, Cannes, France, November 7-9, 2016, Revised selected papers /: 15th International Conference, CARDIS 2016, Cannes, France, November 7-9, 2016, Revised selected papers. (2017) - Unknown
No abstract available